1998
DOI: 10.1042/bj3330549
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of two amino acid transport activities in 4F2 heavy chain- expressing Xenopus laevis oocytes

Abstract: Expression of the type II membrane proteins of the rbAT/4F2hc family in Xenopus laevisoocytes results in the induction of amino acid transport activity. To elucidate the mechanism of action, amino acid transport was investigated in oocytes expressing the surface antigen 4F2hc. Leucine transport was mediated by a Na+-independent and a Na+-dependent transport mechanism. Both systems could be further discriminated by their stereochemical constraints. Isoleucine, with a branch at the β-position, shared only the Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
(45 reference statements)
2
18
1
Order By: Relevance
“…This observation is in line with findings from Friesema et al [13], who reported that uptake of iodothyronines by endogenous transporters in oocytes seems to be at least partially sodium dependent. In addition, this correlates to the already mentioned findings where the presence of a sodium-dependent LAT-like transporter in oocytes was reported [21]. …”
Section: Discussionsupporting
confidence: 74%
“…This observation is in line with findings from Friesema et al [13], who reported that uptake of iodothyronines by endogenous transporters in oocytes seems to be at least partially sodium dependent. In addition, this correlates to the already mentioned findings where the presence of a sodium-dependent LAT-like transporter in oocytes was reported [21]. …”
Section: Discussionsupporting
confidence: 74%
“…It has been shown that the aromatic amino acids Tyr and Trp, which can be transported by both systems L and T, inhibit the uptake of T 3 in neonatal cardiomyocytes and transfected Xenopus oocytes (Everts et al 1996b, Ritchie et al 1999. Only system L is sensitive to the synthetic amino acid analogue BCH (Broer et al 1998, Ritchie et al 1999. Our results show that uptake of T 3 was not sensitive to BCH, from which we conclude that system L does not participate in uptake of T 3 in neonatal rat cardiomyocytes.…”
Section: Discussionsupporting
confidence: 46%
“…125 I]T 3 , cardiomyocytes were preincubated and incubated (15 min) with 0·5 or 2 mM Trp, 0·5 or 2 mM Tyr (substrates for system T and L) or 5 mM BCH, a specific system L inhibitor (Broer et al 1998) (Fig. 4).…”
Section: To Test the Possible Involvement Of Amino Acid Transport Sysmentioning
confidence: 99%
“…Similar, but more complex is the situation for the amino acid transport systems found after expression of the glycoproteins rBAT (related to b 0,+ amino acid transport) and 4F2hc (4F2 heavy chain, CD98). Expression of 4F2hc in Xenopus oocytes induces at least two distinct amino acid transport activities (corresponding to the amino acid transport systems L and y + L) [38]. This observation was explained after the identification of a new family of amino acid transporters [39].…”
Section: Interaction Of Expressed Proteins With Endogenous Proteinsmentioning
confidence: 99%